SELF-DIRECTED FEEDBACK: AN ATTEMPT TOWARDS LEARNER AUTONOMY IN WRITING - Tsara Desiana Akmilia; Pupung Purnawarman; Rojab Siti Rodliyah (Indonesian EFL Journal, 2015)
This paper aims to investigate the application of self-directed feedback in a writing classroom in terms of how it may affect their skills in writing and the students’ response to it. The study was conducted in one of public high schools in Bandung, taking nine students of a science class as the participants. It employs a case study which is using interview and document analysis as the data collection techniques. The findings show that after the inclusion of self-directed feedback in four drafts, the students managed to have a progress in terms of organization, vocabulary, mechanics, and grammar in the process of writing a report text. The awareness of their own progress also indicates a trait of an autonomous learner. Most of the students saw self-directed feedback as a worthy technique to be used again in the subsequent lessons. As a conclusion, self-directed feedback is proven applicable in the writing classrooms as it functions as a step in making students acquire strategies of learning autonomy. For further research, it is suggested that self-directed feedback is included in a set of a self-monitoring strategy rather than one exclusive technique.Keywords: self-directed feedback, writing, learner autonomy